Mnemonic Storytelling as a Psycholinguistic Approach to Enhancing Arabic Writing Competence - Nur Hanifansyah; Menik Mahmudah; Sultan Abdus Syakur (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
Imagine a classroom where Arabic writing, often perceived as a rigid and intimidating skill, transforms into an engaging narrative journey filled with vivid stories and emotional connections. What if students could master complex grammatical structures and expand their vocabulary not through rote memorization, but by weaving them into unforgettable tales? This study breaks conventional norms by introducing mnemonic storytelling as a revolutionary psycholinguistic strategy to enhance Arabic writing competence among students at Darullughah Wadda’wah Islamic Boarding School. The research employs a qualitative approach, involving 30 students aged 16–18 years, selected through purposive sampling. Over six weeks, participants engaged in weekly mnemonic storytelling sessions, integrating key grammatical rules and vocabulary into culturally rich narratives. Data were collected via observations, semi-structured interviews, and analysis of writing samples. The findings reveal significant improvements in grammar retention, vocabulary acquisition, and creative expression, underscoring the effectiveness of mnemonic storytelling as an emotionally engaging and cognitively efficient teaching tool. This study not only redefines how Arabic writing is taught but also advocates for storytelling as a core pedagogical strategy. Future research should explore its adaptability across diverse educational settings to amplify its impact on language education.